2017
DOI: 10.1371/journal.pone.0180436
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent health in rural Ghana: A cross-sectional study on the co-occurrence of infectious diseases, malnutrition and cardio-metabolic risk factors

Abstract: In sub-Saharan Africa, infectious diseases and malnutrition constitute the main health problems in children, while adolescents and adults are increasingly facing cardio-metabolic conditions. Among adolescents as the largest population group in this region, we investigated the co-occurrence of infectious diseases, malnutrition and cardio-metabolic risk factors (CRFs), and evaluated demographic, socio-economic and medical risk factors for these entities. In a cross-sectional study among 188 adolescents in rural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…These imply that a large number of these children were likely to be micronutrients deficient at different degrees and their consequences, including poor health and neurodevelopmental outcomes. Previous studies in Ghana (Alicke et al, ; Egbi, Alatiah, Ayi, & Steiner‐Asiedu, ) had reported high prevalence of vitamin A deficiency (93.6%, 36.6%) in children aged 6–12 years. The story seems not to change.…”
Section: Discussionmentioning
confidence: 93%
“…These imply that a large number of these children were likely to be micronutrients deficient at different degrees and their consequences, including poor health and neurodevelopmental outcomes. Previous studies in Ghana (Alicke et al, ; Egbi, Alatiah, Ayi, & Steiner‐Asiedu, ) had reported high prevalence of vitamin A deficiency (93.6%, 36.6%) in children aged 6–12 years. The story seems not to change.…”
Section: Discussionmentioning
confidence: 93%
“…In the 2014 Ghana Demographic and Health Survey (GDHS) report [ 8 ], 15–19 years adolescents boys compared to their female peers were reported to have a higher prevalence of stunting and underweight while the girls had a higher overweight prevalence. Emerging data from Ghana has also shown varied and relatively higher prevalence rates of stunting (15–50.3%), underweight (7–19.4%), and overweight/obesity (6.9–17%) among adolescent males and females depending on the context in which the study was conducted [ 9 , 10 , 11 , 12 ]. Although these studies are limited by their cross-sectional design and geographical scope, which mainly includes the metropolitan areas of Accra and Kumasi; the general conclusion is that Ghanaian adolescent boys are often worse off regarding stunting and underweight compared to their female peers.…”
Section: Introductionmentioning
confidence: 99%
“…Between June and August 2015, 200 adolescent boys and girls from the Agogo 2000 birth cohort were reassessed and underwent a health check-up as part of the follow-up on the impact of gestational malaria on health outcomes [ 26 ]. The inclusion criteria for this cross-sectional study were turning 15 in the year that the study was conducted, informed written consent, absence of pregnancy and no previous diagnosis of type 1 diabetes [ 13 ]. After excluding participants with implausible values ( n = 1), without plasma carotenoid measurements ( n = 1), and one of each twin-pair ( n = 9) to avoid bias in the gene frequency, the final number of 189 adolescents were included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Alicke et al previously analyzed data of 188 adolescents from the Agogo 2000 birth cohort study to characterize “the co-occurrence of infectious diseases, malnutrition and cardio-metabolic risk factors” in rural Ghana. In this population, more than one-third (36%) had VAD, and the median plasma retinol concentration was 0.77 (IQR: 0.49–1.05) µmol/L [ 13 ]. However, the total plasma carotenoid concentrations (median: 2.8 (2.2–3.8) µmol/L) and β-carotene concentrations (1.49 (1.12–2.22) µmol/L) were three times higher than the reference values [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%